ANALGETIC ACTIVITY DETERMINATION OF PAPAYA LEAVES (Carica papaya L.) AND BASIL LEAVES (Ocimum sanctum L.) EXTRACTED USING NATURAL DEEP EUTECTIC SOLVENT - Renny Amelia; Yuniarti Falya; Tomi; Daryuti; Eka Umi Barkah (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Natural deep eutectic solvents (NaDES) are obtained from an adequate mixture of hydrogen bond acceptors (HBA) and donors (HBD), which can bond through the interaction of hydrogen bonds to form a eutectic with a low melting point. NADES has been implemented in several studies as an effective extraction method, but it is still not widely used. C. papaya leaves and O. sanctum leaves have been widely known to have various pharmacological activities. The aim of this study was to determine the best analgesic ability of the NADES extract of C. papaya and O. sanctum leaves. The extraction process used was Microwave-Assisted Extraction (MAE). The liquid extract was tested for antioxidant activity and analgesic activity using doses of 600 mg/kgBW, 800 mg/kgBW, and 1000 mg/kgBW. The results show that The IC50 values of the NADES extract of C. papaya and O. sanctum leaves were 920 ppm and 882 ppm, respectively. Both analgetic percentages are equivalent to the positive control starting from a concentration of 800 mg/kgBW, where the analgetic percentage of the NADES extract of papaya leaves and basil leaves is 59.80% and 54.57% respectively that included in weak category. It can be concluded that both NADES extracts of papaya and basil leaves have analgetic capabilities. Keywords: Natural Deep Eutectic Solvent (NADES), Carica papaya, Ocimum sanctum, analgetic activity.